1998
DOI: 10.1111/1467-8489.00062
|View full text |Cite
|
Sign up to set email alerts
|

Australian quarantine post the Nairn Review

Abstract: The Commonwealth government has accepted the basic tenets of the report of the Australian Quarantine Review (the ‘Nairn Review’), except for the recommendations to establish a statutory authority. Australia will maintain its existing high standards of quarantine and enhance activities such as community awareness, manageable risk (based on science), protection of Australia’s unique environment, external input to policy formulation, and recognition of the continuum of quarantine (pre‐border, border and post‐bord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…In providing significant funding for quarantine -at a time of overall budgetary stringency -the government demonstrated its commitment to maintaining a strong quarantine system (Tanner and Nunn 1998). Consistent with the government's endorsement of the underlying rationale of the Nairn Review of a 'shared responsibility', two-thirds of the funding has been provided by government, with the remainder being contributed by industry through the application of AQIS's existing full cost-recovery policy.…”
Section: Key Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…In providing significant funding for quarantine -at a time of overall budgetary stringency -the government demonstrated its commitment to maintaining a strong quarantine system (Tanner and Nunn 1998). Consistent with the government's endorsement of the underlying rationale of the Nairn Review of a 'shared responsibility', two-thirds of the funding has been provided by government, with the remainder being contributed by industry through the application of AQIS's existing full cost-recovery policy.…”
Section: Key Outcomesmentioning
confidence: 99%
“…Its recommendations were largely adopted (DPIE 1997) and are now in operation (AQIS 1998, Tanner andNunn 1998). The Nairn Review identified a number of fundamental principles that apply to risk analysis in a range of disciplines and recommended that they should also apply to quarantine import risk analysis.…”
Section: Principles Of Risk Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The Australian Quarantine Act of 1908 is a good example. The Act aimed to 'provide measures for the inspection, exclusion, detention, observation, segregation, isolation, protection, treatmen~, sanit~ry regulation and disinfection of vessels, installations, persons, goods, things, animals or plants and having as their object the prevention ofthe introduction or spread ofdiseases or pests affecting human beings, animals and plants' (Tanner and Nunn, 1998). However, although the means to regulate imports were available, prior to the 1950's quarantine of plants, both in agriculture and forestry, was very poor (Empire Forestry Association, 1948a ' Eldridge and Simpson, 1987;Walker, 1987;Wylie: 1989;Old and Dudzinski, 1998).…”
Section: Forestry and Quarantinementioning
confidence: 99%
“…During the course of the last century, quarantine has evolved from virtually non-existent during the Second World War, to exclusion policies in the 1950-70's and ultimately to modem quarantine practices based on manageable risk concepts (Wylie, 1989;Tanner and Nunn, 1998). Today, quarantine involves not only Government regulations, but also public education.…”
Section: Forestry and Quarantinementioning
confidence: 99%